Episodic and Chronic Migraine in Primary Care. Issue 7 (29th April 2019) - Young, Nathan P.; Philpot, Lindsey M.; Vierkant, Robert A.; Rosedahl, Jordan K.; Upadhyaya, Sudhindra G.; Harris, Ann; Ebbert, Jon O.
Abstract : Objective: To inform migraine care model development by assessing differences between patients with chronic migraine (CM) and episodic migraine (EM) in the current state of treatment, disability, patient satisfaction, and quality improvement opportunities. Background: Efficient and focused use of scarce resources will be needed to address challenges within large populations of migraine patients. Methods: We deployed a cross‐sectional survey study of randomly selected migraine patients within a community primary care practice. Results: There were 516 survey respondents (516/1804 [30%] response rate). CM patients were more likely than EM patients to report care from a neurologist (76/110 [69%] vs 229/406 [56%]; P  = .0026), and higher disability according to the Migraine Disability Assessment and Headache Impact Test – 6 questionnaires ( P  < .0001). CM patients were less likely than EM patients to report overall satisfaction with care (16/110 [38%] vs 156/406 [66%], P  = .0002), satisfaction with access to care (17/110 [33%] vs 176/406 [68%], P  < .0001), and advice they needed (16/110 [31%] vs 160/406 [62%], P  < .0001). Most patients with migraine had been offered triptan medications 377/516 (78%). Overall, 156/516 (31%) of individuals were currently taking any medication for migraine prevention, and 208/516 (40%) including botulinum toxin injections. CM patients were more likely to be taking preventive medication (39/110 [36%] vs 117/406 [29%], P  = .0191) and report familiarity with the diagnosis of medication‐overuse headache than patients with EM (80/110 [81%] vs 256/406 [69%], P  = .0178). Conclusions: We observed differences between patients with chronic and EM and expected care delivery improvement opportunities for migraine patients in primary care. CM patients report higher levels of disability and less satisfaction with access to perceived needed medical advice and care. These findings support the need to further develop and study novel care models to efficiently and effectively deliver high‐quality care and expertise in limited supply to a diverse migraine population.